Induction of Cycloheximide-Resistant Mutants in Saccharomyces cerevisiae with N-Methyl-N′-Nitro-N-Nitrosoguanidine and ICR-170 - Brusick, David J. (1972)
N-Methyl-N′-nitro-N-nitrosoguanidine (MNNG) induces cycloheximide-resistant mutations in Saccharomyces cerevisiae, but few, if any, resistant mutants are induced by the acridine mustard ICR-170. Cycloheximide sensitivity in yeast is associated with the ribosome, and treatment with the antibiotic at concentrations of 2 μg/ml results in complete inhibition of protein synthesis. Missense mutations induced by MNNG probably lead to the loss of cycloheximide binding sites on the ribosome, resulting in resistance to the antibiotic without altering the activity of the organelle in protein synthesis. ICR-170, however, induced primarily frameshift mutations that would alter ribosome structural integrity, resulting in cell death rather than resistance. ICR-170 and MNNG are both mutagenic in a system in which base-pair substitution and frameshift mutations can be detected. These results indicate that cycloheximide resistance in S. cerevisiae, like streptomycin and spectinomycin resistance in Escherichia coli, can be induced by base-pair substitution mutagens but not by frameshift mutagens such as ICR-170.